Characterization and Comparison of the Human and MouseGLC1A Glaucoma Genes - Fingert, John H.; Ying, Lihua; Swiderski, Ruth E.; Nystuen, Arne M.; Arbour, Nancy C.; Alward, Wallace L.M.; Sheffield, Val C.; Stone, Edwin M.

(untitled) (Genome Research, 1998)
The GLC1A gene (which encodes the protein myocilin) has been associated with the development of primary open angle glaucoma. Bacterial artificial chromosomes containing the human GLC1Agene and its mouse ortholog were subcloned and sequenced to reveal the genomic structure of the genes. Comparison of the coding sequences of the human and mouse GLC1A genes revealed a high degree of amino acid homology (82%) and the presence of several conserved motifs in the predicted GLC1A proteins. The expression of GLC1A was examined by Northern blot analysis of RNA from adult human tissues.GLC1A expression was observed in 17 of 23 tissues tested, suggesting a wider range of expression than was recognized previously. The comparison of the human and mouse GLC1A genes suggests that the mouse may be a useful model organism in studying the molecular pathophysiology of glaucoma.[The sequence data described in this paper have been submitted to the GenBank data library under accession nos. AF049791–AF049796.]